Subsidiary redefinition: Charter loss in a German-owned subsidiary in Hungary - Christoph Dörrenbächer; Jens Gammelgaard (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
Based on a literature review and a single case study approach, this paper provides insights into the actors, interests and dynamics of charter losses. It reports the results of interviews with 20 managers at different units of Siemens ICN (Information & Communication Network division) in Germany, Hungary and Austria, including the Hungarian subsidiary where the charter loss occurred, the German headquarters, and the main competing subsidiaries. Furthermore, the paper sheds light on the questions: to what extent and by what combination of host country, subsidiary-related and MNC structural and organizational factors do situations develop in which a subsidiary loses its charter. Our findings show that there is no single reason for a charter loss, but multiple interdependent reasons subject to divergent interpretations, reflecting the micropolitical interests of the key actors. The case study further elucidates that there is room for strategic action at the subsidiary level to avert a charter loss, whereby anticipatory adjustment of the subsidiary towards more balanced internal and external embeddedness as well as constant interpersonal networking with the headquarters office are two important prerequisites. – – Dieser Beitrag beschäftigt sich auf Basis einer Fallstudie mit der Frage, warum Tochtergesellschaften multinationaler Unternehmen Mandate verlieren. Mandate sind zeitlich und inhaltlich befristete, von der Unternehmenszentrale eines multinationalen Unternehmens verliehene oder von einzelnen Tochtergesellschaften errungene Kompetenzen bzw. Verantwortlichkeiten, die die konzerninterne Arbeitsteilung in einem multinationalen Unternehmen definieren. Es werden Ergebnisse aus Interviews mit mehr als 20 Managern der Siemens- Sparte für Vermittlungstechnik (Information and Communications Networks oder kurz ICN) in Deutschland, Ungarn und Österreich präsentiert. Der Beitrag verdeutlicht, dass es verschiedene interdependente Ursachen für Mandatsverluste gibt, die je nach den mikro-politischen Interessen der wesentlichen Akteure unterschiedlich interpretiert werden. Die Fallstudie verweist zugleich auf Spielräume für strategisches Handeln auf der Tochtergesellschaftsebene. Wesentliche Ansatzpunkte sind dabei eine strategische Ausbalancierung von interner und externer Eingebundenheit der Tochtergesellschaft sowie eine stark auf interpersonelle Kontakte abstellende Vernetzung der Tochtergesellschaftsmanager mit der Konzernzentrale.
Keywords: 300